A novel proceduralized donor liver back-table preparation technique minimizes hemorrhage following liver implantation in orthotropic liver transplantation - Tang, Rui; Wu, Guangdong; Tong, Xuan; Yu, Lihan; Li, Ang; Lin, Jingyi; Xu, Guangxun; Lu, Qian (Frontiers in Surgery, 2024)
BackgroundIntraoperative hemorrhage is one of the major complications of orthotopic liver transplantation (OLTX) and is mainly caused by technical difficulties of the surgical procedure besides primary liver diseases. The present study aimed to evaluate the feasibility and clinical effects of a novel proceduralized donor liver back-table preparation (DLBTP) technique for use in OLTX.MethodsThis retrospective study was conducted between January 2018 and June 2020 based on patients who had undergone OLTX. All livers transplanted using the reported back-table procedures were defined as the control group A (n = 43), while those prepared using our new procedure as the experimental group B (n = 160). The first-hand surgical experience of transplant surgeons was surveyed in a post hoc comparative analysis.ResultsDLBTP time was significantly longer and the probability of low-quality hepatic artery skeletonization was lower in group B compared to group A patients. Compared to group A, the time for hemorrhage control was shorter [P < 0.05, 0.3 h (range, 0.17–0.58 h)], and the degree of blood loss was less [P < 0.05, 60 ml (range, 30–240 ml)] in group B. Major bleeding sites were soft tissue of the hepatic hilum and the wall of the inferior vena cava. Due to trimmed soft tissue in the first porta hepatis region, there was less blood oozing, making it easier to stem the bleeding and construct anastomosis.ConclusionAlthough the procedural DLBTP for OLTX was time-consuming, the new procedure significantly reduced the degree of hemorrhage and the time required to control bleeding.